Review paper Application of tacrolimus in the treatment of skin diseases other than atopic dermatitis - Silny, Wojciech; Sadowska, Anna; Dańczak-Pazdrowska, Aleksandra; Polańska, Adriana (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
In dermatological therapy, a basic group of drugs with immunosuppressive and anti-inflammatory effects is the glucocorticoids. Their mechanism of action may lead to numerous side effects. The discovery of cyclosporin A, tacrolimus and pimecrolimus has created an alternative to steroid therapy in dermatology. A common feature of calcineurin inhibitors is inhibition of the activity of immunocompetent cells, which are responsible for inflammatory processes in the human body. Most studies on this group of drugs concern their effectiveness in the treatment of atopic dermatitis (AD). This paper presents a review of the literature concerning the use of tacrolimus in therapy of diseases other than AD.